METAPHORICAL TRANSLATION STRATEGIES OF BAHASA INDONESIA INTO ENGLISH ON CONTEMPORARY INDONESIAN POETRY TRANSLATED BY HARRY AVELING - Harry Sambayu (Universitas Asahan, 2019)
Translation is a process to transfer meaning from Source Language into Target Language. In works, figurative language or metaphor is a problem in translation activities where we asked is not only catch the literal meaning but also the figure and the sense with equivalent both languages. Metaphorical translation strategies aim to serve the reader to able to comprehend the meaning with the sense and esthetical aspect in SL and TL. The differentiation of cultural both SL and TL is core problem from a translator to bridge this. To cover this a translator should has enough knowledge about grammatical aspect and cultural aspect in SL and TL.Keyword : Translation, Metaphor, Metaphorical translation strategies.